2005
DOI: 10.1111/j.1467-9450.2005.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of the Swedish Scholastic Aptitude Test by means of the Swedish Enlistment Battery

Abstract: The construct validity of the Swedish Scholastic Test (SweSAT), used for admissions to higher education, was studied through relating it to the Computerized Enlistment Battery (CAT-SEB) used at conscription to military service. Out of three male age cohorts tested at 18 years with the CAT-SEB in 1997, 1998, or 1999 six groups of men that had taken their first SweSAT in the Autumn (n= 3,163; 2,938; 2,820) the same year, or in the Spring (n= 3,238; 2,587; 2,447) the next year were used for the analyses. Four typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Instead, a number of broader or more specific abilities may be thought of as forming a hierarchal structure. A frequently used threelevel model (see, e.g., Carlstedt & Gustafsson, 2005;Carroll, 1993;Gustafsson, 1988) has at its apex one single general or ''third-order'' factor (Gen) influencing overall performance. At the intermediate level, there are less general ''second-order'' factors related to a number of broad abilities, whereas ''first-order'' factors represent narrow and special abilities (see Figure 1, left model).…”
Section: Rationalementioning
confidence: 99%
“…Instead, a number of broader or more specific abilities may be thought of as forming a hierarchal structure. A frequently used threelevel model (see, e.g., Carlstedt & Gustafsson, 2005;Carroll, 1993;Gustafsson, 1988) has at its apex one single general or ''third-order'' factor (Gen) influencing overall performance. At the intermediate level, there are less general ''second-order'' factors related to a number of broad abilities, whereas ''first-order'' factors represent narrow and special abilities (see Figure 1, left model).…”
Section: Rationalementioning
confidence: 99%
“…[17][18][19] Briefly, the word recollection test assessed knowledge of synonyms (that is, the ability to determine which of four alternatives was the synonym of a given word), the visuospatial geometric perception test assessed the ability to correctly identify a three dimensional object from a series of two dimensional drawings, the logical/inductive performance test assessed the capacity to understand written instructions and apply them to a problem solving task, and the theoretical/technical test assessed mathematical/physics problem solving. The maximum score for the first three tests was 40 points, and that for the theoretical/technical test was 52 points.…”
Section: Cognitive Function Testsmentioning
confidence: 99%
“…31 Small differences also existed in the tests administered at ages 13 and 18 years, and the test for inductive ability at age 18 years was different for the 1977 cohort than for the other cohorts. Although these tests are well validated by psychometric research 31 and demonstrated good predictive validity in this sample (intraindividual correlations between scores at ages 13 and 18 years within domains all exceeded 0.65), we cannot be certain of the exact equivalence of the tests. We should also be cautious in drawing parallels between the findings on these tests and the results from other studies using more standardized cognitive tests.…”
Section: Validity Of Cognitive Testsmentioning
confidence: 99%